2010
DOI: 10.1586/erc.10.127
|View full text |Cite
|
Sign up to set email alerts
|

Current status of the Xience V®everolimus-eluting coronary stent system

Abstract: The introduction of drug-eluting stents has led to a marked reduction of restenosis, which is a major limitation of percutaneous coronary intervention for coronary artery disease. The next-generation Xience V® (Abbott Vascular, CA, USA) everolimus-eluting stent was designed to address the limitations of first-generation drug-eluting stents. The cobalt-chromium stent platform with an open-cell design offers excellent deliverability. Moreover, the combination of a thin fluoropolymer eluting the antirestenotic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The PtCr stent series included four stent models across the range of diameters to attempt more uniform drug distribution and plaque scaffolding. All the mechanical and design characteristics of the CoCr‐EES platform were already detailed in the literature .…”
Section: Methodsmentioning
confidence: 99%
“…The PtCr stent series included four stent models across the range of diameters to attempt more uniform drug distribution and plaque scaffolding. All the mechanical and design characteristics of the CoCr‐EES platform were already detailed in the literature .…”
Section: Methodsmentioning
confidence: 99%
“…In contemporary practice, limus-eluting DES, including those eluting everolimus, biolimus A9, zotarolimus, and sirolimus, are used worldwide and have been shown to effectively inhibit neointimal hyperplasia after stent implantation [10][11][12][13][14][15]. However, data from experimental studies have suggested that different limus drugs may have differential effects on re-endothelialization and subsequently on vascular healing [16,17]. Indeed, a preclinical study has shown more rapid endothelialization with everolimuseluting stent (EES) compared with sirolimus-eluting stent (SES) [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, data from experimental studies have suggested that different limus drugs may have differential effects on re-endothelialization and subsequently on vascular healing [16,17]. Indeed, a preclinical study has shown more rapid endothelialization with everolimuseluting stent (EES) compared with sirolimus-eluting stent (SES) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Drug-eluting stents, bare metal stents which contain an antiproliferative drug [14], have decreased restenosis rates by a relative 50% to 80% [21]. However, first generation drug-eluting stents have been shown to have an increased risk of late stent thrombosis [22] and long-term clinical data of next-generation devices is still unavailable [23].…”
Section: Stenting Complications and Tissue Prolapsementioning
confidence: 99%